2017
DOI: 10.1371/journal.pone.0178587
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of deep vein thrombosis and pulmonary thromboembolism in patients with aortic aneurysms: A nationwide cohort study

Abstract: Studies on the association between aortic aneurysm (AA) and the subsequent risk of venous thromboembolism (VTE) are limited to a few case reports and investigations which only focused on surgical effects. Therefore, we used the National Health Insurance Research Database to clarify whether patients with AAs have a heightened risk of subsequent VTEs, including deep vein thrombosis (DVT) and pulmonary embolism (PE). Our retrospective cohort study comprised patients aged ≥ 18 years who received a diagnosis of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…As such, there is scarcity in the literature of such cases and optimal management. A cohort study by Lee et al 4 found that an aortic aneurysm serves as a risk factor for the development of DVT 4. Kuivaniemi et al 5 suggested this phenomenon was likely to be due to triggering of an inflammatory reaction following the degeneration of the tunica media within the aorta 5.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is scarcity in the literature of such cases and optimal management. A cohort study by Lee et al 4 found that an aortic aneurysm serves as a risk factor for the development of DVT 4. Kuivaniemi et al 5 suggested this phenomenon was likely to be due to triggering of an inflammatory reaction following the degeneration of the tunica media within the aorta 5.…”
Section: Discussionmentioning
confidence: 99%
“…These developments correspond with the decline in smoking rates among men, as well as the implementation of screening programs and subsequent uptake in elective repairs [ 15 , 20 ]. Less common complications of AAAs include aortoenteric or aortocaval fistulae and iliac vein compression resulting in deep vein thrombosis or emboli [ 40 , 41 , 42 ].…”
Section: Clinical Presentation and Course Of Diseasementioning
confidence: 99%
“…Ebenfalls ist ein Fall von einseitiger Bein-schwellungdurcheinAAA mitaortokavaler Fistel beschrieben [10]. Im Vergleich zur gesunden Allgemeinbevölkerung haben Patienten mit Aortenaneurysmen ein 1,88fach erhöhtes Risiko für eine TVT, wobei eine abdominelle Aneurysmamanifestation im Gegensatz zur thorakalen das Risiko noch weiter erhöht [4].…”
Section: Therapie Und Verlaufunclassified